Electro-Mechano-Fluidic Modeling of Microsystems Using Finite Elements - Rochus, Veronique (2012)
Strong couplings between the mechanical, electric, magnetic, fluidic and thermal fields exist in the behaviour laws describing microsystems. Also, due to the large surface/volume ratio, surface forces such as the electrostatic force and fluid damping become predominant. This paper presents the modeling and simulation of electrically-actuated micro-systems taking the electro-mechano-fluidic coupling into account. A micro-resonator consisting in a cantilever beam suspended over a substrate is modeled, and finite-element simulations are validated with experimental measurements.